Legibility Level of STEM Mobile Learning Package on Ecosystem - Ngabekti, Sri; Budi Prasetyo, Andreas Priyono; Hardianti , Risa Dwita (KnE Social Sciences, 2019)
STEM in education has been discussed as an approach that enhances students to demonstrate their holistic knowledge in some projects given. Teacher could support STEM in learning process by providing students proper learning material such as learning environment, learning resources, and medias. This research aimed to test legibility level of texts uploaded on STEM Mobile Learning Package (STEM MLP) on ecosystem as one of students’ learning resources. Legibility level data was obtained from questionnaire from small scale test on 47 students. Data were analyzed descriptively by both qualitative and quantitative methods. The ﬁnding showed that legibilty level from students’ questionnaire ranged from 78,7 percent to 97 percent. In addition,FryGraphanalysisshowedthattextsinSTEMMLPwereinarea13 Keywords: legibility level, STEM, Mobile Learning